Contemporary study of multiple sclerosis disability in South East Wales. Issue 4 (3rd November 2022) - Harding, Katharine Elizabeth; Ingram, Gillian; Tallantyre, Emma Clare; Joseph, Fady; Wardle, Mark; Pickersgill, Trevor P; Willis, Mark D; Tomassini, Valentina; Pearson, Owen Rhys; Robertson, Neil P
Abstract : Background: A contemporary understanding of disability evolution in multiple sclerosis (MS) is an essential tool for individual disease management and planning of interventional studies. We have used prospectively collected longitudinal data to analyse disability progression and variation in a British MS cohort. Methods: Cox proportional hazards regression was used to estimate hazard of Expanded Disability Status Scale (EDSS) 4.0 and 6.0. A continuous Markov model was used to estimate transitional probabilities for individual EDSS scores. Models were adjusted for age at MS onset, sex and disease-modifying treatments (DMTs) exposure. Results: 2135 patients were included (1487 (70%) female, 1922 (89%) relapsing onset). 865 (41%) had used DMTs. Median time to EDSS 4.0 and 6.0 was 18.2 years (95% CI 16.3 to 20.2) and 22.1 years (95% CI 20.5 to 24.5). In the Markov model, the median time spent at EDSS scores of <6 (0.40–0.98 year) was shorter than the time spent at EDSS scores of ≥6 (0.87–4.11 year). Hazard of change in EDSS was greatest at EDSS scores <6 (HR for increasing EDSS: 1.02–1.33; decreasing EDSS: 0.34–1.27) compared with EDSS scores ≥6 (HR for increasing EDSS: 0.08–0.61; decreasing EDSS: 0.18–0.54). Conclusions: These data provide a detailed contemporary model of disability outcomes in a representative population-based MS cohort. They support a trend of increasing time to disability milestones compared with historical reference populations, and document disability variation with the use of transitional matrices. In addition, they provide essential information for patient counselling, clinical trial design, service planning and offer a comparative baseline for assessment of therapeutic interventions.